Hydrogen-Bonded Networks Based on Cobalt(II), Nickel(II), and Zinc(II) Complexes of N, N'-Diethylurea. (27th June 2010) - Drakopoulou, Labrini; Raptopoulou, Catherine P.; Terzis, Aris; Papaefstathiou, Giannis S.
Abstract : N, N'-diethylurea (DEU) was employed as a ligand to form the octahedral complexes [ M ( DEU ) 6 ] 2 + (M=Co, Ni and Zn). Compounds [ Co ( DEU ) 6 ] ( BF 4 ) 2 (1 ), [ Co ( DEU ) 6 ] ( CIO 4 ) 2 (2 ), [ Ni ( DEU ) 6 ] ( CIO 4 ) 2 (3 ), and [ Zn ( DMU ) 6 ] ( CIO 4 ) 2 (4 ) have been prepared from the reactions of DEU and the appropriate hydrated metal(II) salts in EtOH in the presence of 2, 2-dimethoxypropane. Crystal structure determinations demonstrate the existence of [ M ( DEU ) 6 ] 2 + cations and CIO 4 - (in 2–4 ) or BF 4 - (in 1 ) counterions. The [ M ( DEU ) 6 ] 2 + cations in the solid state are stabilized by a pseudochelate effect due to the existence of six strong intracationic N-H ⋯ O ( DEU ) hydrogen bonds. The [ M ( DEU ) 6 ] 2 + cations and counterions self-assemble to form hydrogen-bonded 2D architectures in 2–4 that conform to the kgd (kagome dual) network, and a 3D hydrogen-bonded rtl (rutile) network in 1 . The nature of the resulting supramolecular structures is influenced by the nature of the counter-ion. The complexes were also characterized by vibrational spectroscopy (IR).